Structural changes and drivers of agrifood system growth in Tajikistan - Khakimov, Parviz; Diao, Xinshen; Goibov, Manuchehr; Ashurov, Timur (International Food Policy Research Institute, 2025)
The agricultural sector accounted for one-third and one-fourth of total GDP in 2011 in 2022, respectively. In 2022 compared to 2011, both primary and off farm agricultural GDPs dropped, respectively by 13.2 and 3 percentage points, while primary agriculture employment share fell by 10.4 percentage points. The domestic market played a vital role in the recent agrifood system (AFS) growth, and a sizable portion of locally produced agrifood products was able to meet domestic demand. Though agroprocessing an important off-farm component of the AFS, grew more rapidly and thus contributed the most to off farm AFS growth, the aggregate size of off-farm components of the AFS did not increase to match with the structural change in the broader economy.